CONTROVERSIES ON ARMS TRADE AND HUMAN SECURITY IN THE MIDDLE EAST - Mitayani, Nawang; Surwandono, Surwandono (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2024)
The security of the Middle Eastern countries is impacted by the arms trade in the region. Human rights breaches in the Middle East are partly caused by the armaments trade. Currently, one of the primary goals in defending the nation against external threats is obtaining weapons. . The article  examine the Middle East's armaments trade and its impact on human security that analyzed with liberal theory. Descriptive qualitative research methodology was employed in this study. The information was gathered from research-related publications, websites, and other sources. This article finds that the massive arms trade in the Middle East is reducing the quality of human security, in the context of the absorption of welfare funds for arms purchases.